The United States balance of payments : statements by economists, bankers and others, on the Brookings Institution study, "The United States balance of payments in 1968" - United States; Brookings Institution (Washington : U.S. Govt. Print. Off., 1963)
On July 29 and 30, 1963, the Joint Economic Committee held hearings on the outlook for the U.S balance of payments. These hearings were devoted principally to a study prepared under the direction of Walter S. Salant of the Brookings Institution.
At head of title: 88th Cong., 1st sess. Joint committee print.
Includes bibliographic footnotes
usc 06/06/18
Loans
Keywords: Balance of payments; United States